Women's Trauma Due to Sexual Harassment in Public Spaces (Study at UPTD PPA DP3A Semarang City) - Mazin, Roafa Nabila; Elizabeth, Misbah Zulfa (International Journal of Social Service and Research, 2025)
Sexual harassment in public spaces has become a critical social issue affecting women's safety and well-being in urban environments. This study examines the forms, psychological impacts, and societal responses to sexual harassment experienced by women in public spaces in Semarang City, Indonesia. Utilizing a qualitative phenomenological approach, data were collected through in-depth interviews with two key informants from UPTD PPA DP3A Semarang City—administrative officers and victim companions—alongside relevant documentation. Analysis was conducted using the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The study reveals that common forms of harassment include groping, thigh and breast squeezing, and breast assault. Victims exhibit freeze responses, crying, and screaming as immediate reactions. Findings demonstrate that patriarchal culture significantly influences perpetrator behavior by objectifying women's bodies. Victims face severe consequences, including victim blaming, social discrimination, post-traumatic stress disorder (PTSD), anxiety, depression, diminished social relationship quality, sleep disorders, and physical injuries. Analyzed through George H. Mead's symbolic interactionism theory, the research exposes how societal symbols and meanings reinforce gender-based violence and trauma. This study contributes to understanding the intersection of public space safety, gender inequality, and trauma psychology, offering implications for policy development and victim support systems.